KONTRIBUSI SOSIOLOGI PADA DUNIA PENDIDIKAN DAN PERKEMBANGAN DI INDONESIA - indasah (Bahasa Indonesia, 2024)
Abstrak: The aim of this research is to undertand the contribution of sociology to the world of education and its development in Indonesia. The method used qualitative research. Data is analyzed using steps: data presentation, data filtering, classification, and inference. Research results can be concluded as follows: (1) The contribution of sociology to the world of education, namely students, teachers, supervisors, principals, and supervisors, they interach as position holders in a social system that has institutional and organized goals, namely to educate students. (2) Overview of the contribution of sociology to the world of education depars form the fact that the main task of schooling (educational transactions) mainly takes place in a relatively small social system, the classroom. (3) The sociology of education departs form the reality in which the school system is never separated from it external environment as in all organizations, it is also influenced by various external forces. (4) The development of sociology of education in Indonesia includes its history, role in educational institutions, equity issues, multicultural education, the impact of globalization and technology. The discipline continues to contribute to our understanding of social roles in the complex increasingly word of education